Factors Influencing the Occurrence of Preeclampsia in Pregnant Women at Primary Care Clinic - Andoko, Dewanto; Hendrik, Hendrik; Moningkey, Shirley; Soeryani, R Wianti; Sungono, Veli (Faculty of Medicine, Public Health, and Nursing, 2024)
Background: Preeclampsia is a common medical complication during pregnancy, affecting approximately 5-15% of all pregnancies. This research aims to identify factors influencing the occurrence of preeclampsia at a Primary care clinic in Bandar Selamat, Tembung, Medan, in the year 2023. Method: This study adopts a cross-sectional approach, involving pregnant women with a gestational age of ≥20 weeks who visited the primary care clinic in Bandar Selamat, Tembung, Medan, from July to December 2023. A total of 37 respondents were sampled using convenience sampling. The dependent variable was the occurrence of preeclampsia, while independent variables included age, parity, medical history, calcium supplementation, and employment history. Multivariate analysis was conducted using SPSS version 23. Result: 16.8% of the respondents experienced preeclampsia. Additionally, 21.6% were in the unhealthy reproductive age group, 72.9% were primigravida, 13.5% had a medical history, 43.2% had poor calcium supplementation, and 40.5% were employed. Multivariate analysis revealed that Age (P-value: 0.044, OR: 24.5, 95% CI: 1.082 - 556.407), Parity (P-value: 0.252, OR: 4.926, 95% CI: 0.32 - 75.4), History of Chronic Disease (P-value: 0.32, OR: 40.484, 95% CI: 1.37 - 1196.2), Calcium Supplementation (P-value: 0.167, OR: 11.582, 95% CI: 0.3 - 374.8), and Employment Status (P-value: 0.679, OR: 1.849, 95% CI: 0.1 - 33.87) are associated with preeclampsia. Conclusion: There is a significant relationship between age, parity, history of chronic disease, and the occurrence of preeclampsia in pregnant women at the primary care clinic in Bandar Selamat, Tembung, Medan. History of Chronic Disease is the most influential variable (OR: 40.484).